Problematic issues and development of classifications of the main parameters of quality and adherence to pharmacotherapy. Part II: physician adherence to clinical guidelines and official drug labels - Yu. V. Lukina; N. P. Kutishenko; S. Yu. Martsevich; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2024)
The second publication is presented, devoted to the classification of the main parameters of quality and adherence to pharmacotherapy. Despite the fact that patients play a central role in the problem of medical adherence, the role of attending physicians is extremely significant both in prescribing/non-prescribing proven effective and safe therapy, and in influencing patient medical adherence. This led to the identification of a special commitment type — the physician adherence to the basic principles of rational treatment. Collection, analysis and systematization of information, as well as the related development of a classification of physician adherence/non-adherence were the aim of this review and analytical work. We searched data using keywords among Russian and English-language sources. When compiling the classification, categories of adherence/non-adherence were identified in accordance with the implementation by physicians of the main provisions of clinical guidelines for long-term therapy for patients with non-communicable diseases (NCDs), as well as following official drug labels reflecting data on clinical pharmacology, the main side effects, drug-drug interactions. The classification of physician adherence/non-adherence to implementing the principles of rational treatment of patients with NCDs can be used in the development of electronic medical decision support systems for providing therapy with proven effectiveness and safety in specific clinical situations. In addition, on the basis of the developed classification, checklists for monitoring by healthcare specialists of the implementation of the rational treatment of patients with chronic NCDs should be created.